2004
DOI: 10.1080/00288233.2004.9513566
|View full text |Cite
|
Sign up to set email alerts
|

The calcium requirements of pastures in New Zealand: A review

Abstract: Calcium (Ca) plays a vital role in the structural integrity of soils, plants, and animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Previous studies have concluded that changes in soil pH depend on intrinsic factors such as soil features (Peech, ) including O.M., Ca and Mg contents and exogenous factors such as acid deposition (Mohnen & Wilson, ), industrial effluents and farming practices (Khan, ). In this study, the average values of soil available Ca and Mg were above their corresponding critical values, and a significant positive correlation was found between the soil pH and exchangeable Ca (Figure ), which is in agreement with the results of Bolton (), Edmeades & Perrott () and Kozak et al . ().…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have concluded that changes in soil pH depend on intrinsic factors such as soil features (Peech, ) including O.M., Ca and Mg contents and exogenous factors such as acid deposition (Mohnen & Wilson, ), industrial effluents and farming practices (Khan, ). In this study, the average values of soil available Ca and Mg were above their corresponding critical values, and a significant positive correlation was found between the soil pH and exchangeable Ca (Figure ), which is in agreement with the results of Bolton (), Edmeades & Perrott () and Kozak et al . ().…”
Section: Discussionsupporting
confidence: 92%
“…In the 18 th month, both correctives increased P levels down to 0.10 m. Fageria & Baligar (2008) reported linear P increase in Brazilian Oxisols, as pH increased from 5.3 to 6.9. Also, Edmeades & Perrott (2004) observed that liming reduced P adsorption and enhanced P mineralization from organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of Ca in NZ pasture increased with increasing N application rate. The loss of Ca cation was highly correlated with the loss of nitrate N, suggesting that Ca leaching is accompanied by nitrate anion [65].…”
Section: Effect Of Nitrogen Use On Soil Nutrients and Propertiesmentioning
confidence: 93%